2004
DOI: 10.1074/jbc.m407082200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and Specific Ubiquitin Acceptor Sites Are Required for Ubiquitination and Degradation of the IFNAR1 Subunit of Type I Interferon Receptor

Abstract: Ubiquitination, endocytosis, and lysosomal degradation of the IFNAR1 (interferon ␣ receptor 1) subunit of the type I interferon (IFN) receptor is mediated by the SCF ␤-Trcp (Skp1-Cullin1-F-box protein ␤ transducin repeat-containing protein) E3 ubiquitin ligase in a phosphorylation-dependent manner. In addition, stability of IFNAR1 is regulated by its binding to Tyk2 kinase. Here we characterize the determinants of IFNAR1 ubiquitination and degradation. We found that the integrity of two Ser residues at positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
183
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(189 citation statements)
references
References 31 publications
6
183
0
Order By: Relevance
“…Some structural preferences exist for ubiquitin ligation of the targeted proteins such as preferred choice of lysines in α-helices, and then for easily accessible lysines in the loop regions. Our findings add to the growing list that indicates a bias towards a consensus sequence motif for ubiquitination by a given E3 [19][20][21][22][23][24][25]. Moreover, it appears that the E3 targets an accessible surface residue providing the selection process with a conformational recognition mechanism.…”
Section: Receptor Ubiquitination Implicated In Regulation Of Trkb Dowsupporting
confidence: 52%
“…Some structural preferences exist for ubiquitin ligation of the targeted proteins such as preferred choice of lysines in α-helices, and then for easily accessible lysines in the loop regions. Our findings add to the growing list that indicates a bias towards a consensus sequence motif for ubiquitination by a given E3 [19][20][21][22][23][24][25]. Moreover, it appears that the E3 targets an accessible surface residue providing the selection process with a conformational recognition mechanism.…”
Section: Receptor Ubiquitination Implicated In Regulation Of Trkb Dowsupporting
confidence: 52%
“…It is possible that other components of the cell's proteolytic machinery are involved in the degradation of polyubiquitinated 4E-BP1. For example, lysosomes have been demonstrated to degrade a variety of polyubiquitinated proteins (Hicke, 2001;Kumar et al, 2004). However, treatment of Jurkat cells with the lysosomal inhibitor chloroquine did not prevent the calyculin A-induced loss of normal-sized 4E-BP1 or cause any further accumulation of the larger forms (data not shown).…”
Section: Relationship Between Ubiquitination and Association Of 4e-bpmentioning
confidence: 94%
“…Moreover, the susceptibility of such proteins to be processed by this pathway is often controlled by protein phosphorylation. In addition to the now classical cases of the inhibitor of nuclear factor kB (IkB) family (Karin and Ben-Neriah, 2000;Chen, 2005;Krappmann and Scheidereit, 2005) and cyclins (Lin et al, 2006a), other examples of proteins whose (poly)ubiquitination is stimulated by their phosphorylation include the type I interferon receptor IFNAR1 (Kumar et al, 2004), the transcription factor STAT1 (Kim and Maniatis, 1996), the antiapoptotic protein Bcl-2 (Lin et al, 2006b) and bcatenin (Aberle et al, 1997;Orford et al, 1997). On the other hand, phosphorylation can inhibit the ubiquitination of other proteins such as the proto-oncogenes c-jun (Musti et al, 1997;Fuchs et al, 1998), c-fos (Okazaki and Sagata, 1995) and c-mos (Nishizawa et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies against Tyk2 [14], as well as antibodies recognizing total IFNAR1 (EA12 and GB8) or IFNAR1 phosphorylated on Ser535 (in human receptor) or Ser526 (in murine receptor) [10,17] were described previously. Antibody against ubiquitin (FK2 mAb) was from Biomol.…”
Section: Antibodies and Immunotechniquesmentioning
confidence: 99%
“…Turnover of IFNAR1 requires its ubiquitination by the SCF β-Trcp/HOS E3 ubiquitin ligase [8], which recognizes the conserved phosphorylated 534 DSGNYS destruction motif [9]. Previously we reported that phosphorylation of IFNAR1 on Ser535 within this motif (essential for recruitment of β-Trcp) is increased upon stimulation of cells with IFNα [10], and catalytic activation of Tyk2 is required for such an increase [11]. Here we describe ligand-and Tyk2-independent pathway that regulates phosphorylation of IFNAR1 on Ser535 as well as IFNAR1 ubiquitination and degradation.…”
Section: Introductionmentioning
confidence: 99%